DESIGN AND IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM IN PT KARYA MURA NIAGA - Santi Yopie; Angellyn Lim (Universitas Internasional Batam, 2022)
PT Karya Mura Niaga is a company engaged in trading computer equipment that was founded in July 2018 and officially operated since January 2019. PT Karya Mura Niaga is a relatively new company, thus the company still does not have a well-established accounting system and relies on the use Microsoft Excel to manually record transactions. The purpose of this project was to develop and design an accurate and reliable accounting record system that can be implemented by PT Karya Mura Niaga to record transactions in accordance with Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK-ETAP) and the currently enforced regulations by utilizing Microsoft Office Access. The implementation method was done by conducting interviews, observations, documentations, system design and simulation of the system implementation in the company for a duration of three months, starting from 1st September until 31th December 2021. The results of the implementation of this system are personalized recording system for the company, easier, faster and more accurate preparation of financial statements, ease in decision making, more accurate stock reporting and due-date reporting. This system is simple and can be applied in small entities company. For future projects, the system features can be improved and increased in complexity than that in this project, thus it can be implemented by larger companies.